Switzerland : Selected Issues Paper. (IMF Staff Country Reports; Country Report, 2011)
The paper assesses the competitiveness of Swiss exporters, and shows that the effect of nominal exchange rate on trade balance depends on the degree of exchange rate pass-through and on trade elasticities. It highlights that the degree of exchange rate pass-through should also be factored in monetary policy decisions. The authorities are considering legislative changes to strengthen macroprudential oversight by supporting the mutual cooperation between Financial Market Supervisory Authority (FINMA) and Swiss National Bank (SNB) over the financial stability. The scope of the too-big-to-fail (TBTF) proposal should also be broadened to address systematic risk.